Associations of HIV infection with insulin and glucose levels in antiretroviral-naïve Rwandan women: a cross-sectional analysis. Issue 12 (5th December 2013) - Dusingize, Jean Claude; Hoover, Donald R; Shi, Qiuhu; Mutimura, Eugene; Kiefer, Elizabeth; Anastos, Kathryn
Abstract : Objectives: The purpose of these analyses was to determine the associations of HIV infection and related immune dysfunction with a glucose homeostasis in the population of antiretroviral-naïve HIV-infected and uninfected Rwandan women. We hypothesise that insulin resistance and its consequences in the developing countries may be further elevated with HIV infection itself regardless of antiretroviral therapy. Study design: Cross-sectional analysis of a longitudinal cohort. Setting: Community-based women's associations. Participants: In 2005, 710 HIV-infected (HIV positive) antiretroviral naïve and 226 HIV-uninfected (HIV negative) women were enrolled in the Rwanda Women's Interassociation Study and Assessment (RWISA). Clinical and demographic parameters, CD4 count, fasting insulin and glucose levels, anthropometric measurements and Bioelectrical Impedance Analysis (BIA) were obtained. Linear models were fit to log-transformed Homeostasis Model Assessment (HOMA) with results exponentiated back to a multiplicative effect on the original scale. Primary outcome measures: The outcome, insulin resistance, was measured by the HOMA, calculated as fasting insulin (μU/mL)×fasting glucose (mmol/L)⁄22.5. Results: In adjusted models, HIV-positive women were less insulin resistant than HIV-negative; an HIV-positive woman tended to have 0.728 times as much (95% CI 0.681 to 0.861) HOMA than a comparable HIV-negative woman. Among the HIV-positive women, those with CD4 <200 cells/µL tended to have 0.741 times as much HOMA (95% CI 0.601 to 0.912) as did comparable women with CD4 >350 cells/µL. The older age was independently associated with a lower HOMA insulin resistance. After adjusting for body mass index, fat and fat-free mass were not independently associated with HOMA. Conclusions: This study found that HIV infection and more advanced HIV infection (CD4 counts <200 cells/µL) were associated with greater insulin sensitivity in antiretroviral naïve African women. These findings provide baseline information for the interpretation of future studies on the effect of antiretroviral therapy on metabolic insulin sensitivity derangements in African population.